Nanostructured diamond for biomedical applications - Pandey P.C.; Shukla S.; Pandey G.; Narayan R.J. (My University, 2025)
Nanostructured forms of diamond have been recently considered for use in a variety of medical devices due to their unusual biocompatibility, corrosion resistance, hardness, wear resistance, and electrical properties. This review considers several routes for the synthesis of nanostructured diamond, including chemical vapor deposition, hot filament chemical vapor deposition, microwave plasma-enhanced chemical vapor deposition, radio frequency plasma-enhanced chemical vapor deposition, and detonation synthesis. The properties of nanostructured diamond relevant to medical applications are described, including biocompatibility, surface modification, and cell attachment properties. The use of nanostructured diamond for bone cell interactions, stem cell interactions, imaging applications, gene therapy applications, and drug delivery applications is described. The results from recent studies indicate that medical devices containing nanostructured diamond can provide improved functionality over existing materials for the diagnosis and treatment of various medical conditions. © 2021 IOP Publishing Ltd